(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
The aim of this research is to explore current trends and innovations in pediatric neurology, focusing on the early diagnosis, prevention, and management of neurological disorders in children. The study seeks to develop evidence-based approaches that enhance neurodevelopmental outcomes, improve quality of life, and promote integrated multidisciplinary care in pediatric neurological practice.